2015
DOI: 10.1097/rlu.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Differential Alterations of Dopamine Transporter in the Striatum and Midbrain in Patients With Parkinsonian Syndrome

Abstract: These findings indicate that reductions in DaT values in the striatum and MB are not necessarily simultaneous with the process of nigrostriatal denervation, and correlation of DaT values among CA/PT and MB becomes weaker as the denervation becomes more severe. Differential regional DaT loss may indicate differential vulnerability of DaT-containing neurons in these structures or could be in part related to tracer binding to non-DaT targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This concept might also be valid for the other pre‐motor symptoms that correlate with constipation, such as RBD and depression. Previous studies have shown no differences in dopaminergic denervation (DaTSCAN™) in patients with PD with and without RBD, as we found here for constipation . However, anxiety and depression have previously been associated with greater dopaminergic denervation (DaTSCAN™) in PD .…”
Section: Discussionsupporting
confidence: 67%
“…This concept might also be valid for the other pre‐motor symptoms that correlate with constipation, such as RBD and depression. Previous studies have shown no differences in dopaminergic denervation (DaTSCAN™) in patients with PD with and without RBD, as we found here for constipation . However, anxiety and depression have previously been associated with greater dopaminergic denervation (DaTSCAN™) in PD .…”
Section: Discussionsupporting
confidence: 67%
“…We also investigated gene‐delivery efficiency of GO‐PEI‐APNL complexes in vivo using a 6‐OHDA‐induced PD mouse model . Dopamine transporters, such as VMAT2, are reportedly reduced in PD patient brains and the resulting loss of dopamine transporters triggers cognitive deficits and impairs neurotransmitter secretion into synaptic vesicles . In the present study, injection of GO‐PEI‐APNL complexes into 6‐OHDA‐induced PD mouse brains increased TH, DAT, and VMAT2 expression, indicating increased numbers of dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%